Establishing a research agenda for enterprise information management - White, Martin S. (2020)
ABSTRACT Much is being made of the need for organisations to prepare for a ‘new normal’ in the wake of the Covid19 pandemic. This presumes that the ‘normal’ is well understood and that the ‘new normal’ will be a stable position. In reality it may take several years to achieve the ‘new normal’. In the near term organisations will need to support a complex and constantly changing mix of office and remote working. Because there has been so little research into how information has created, stored, discovered, used and shared (the information lifecycle) heretofore there is a substantial risk that changes introduced to ameliorate the impact of Covid19 may not have any substantial impact on improved information management and indeed could be counter-productive. Solutions to support a substantial work-at-home workforce may not be scalable and extensible if a more heterogenous framework of remote + office is found to be optimal. This paper highlights how little is known about how information flows around organisations. It is based on both published research and on the insights and outcomes of over 100 information management consultancy projects. Computational ethnography could become an important research methodology in tracking information flows but there are technical, compliance and ethical issues which need to be addressed by the global research community as a matter of urgency. Experience from research into personal information management and knowledge management should also be taken into account. The paper proposes that every effort should be taken to facilitate exchanges of experience and expertise between academic research and practitioners who need to make business-critical decisions based on high-quality information. Keywords Computational ethnography, enterprise search, ethnography, information management, information risk, information seeking, knowledge management, personal information management. ABOUT THE AUTHOR/S Martin S. White University of Sheffield and Intranet Focus Ltd. Martin.white@intranetfocus.com Martin White is Managing Director, Intranet Focus Ltd (Horsham, UK) and a Visiting Professor at the Information School, University of Sheffield. Over the last two decades he has undertaken a wide range of information management projects for multi-national organisations with complex information management and information discovery challenges. He is the author of four books on enterprise search management. New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s)